Research on cemented artificial pillars to replace protective inter-block coal pillars and stope failure laws - Che, Chiyuan; Cao, Shenggen; Zhao, Changzheng; Du, Shuyu; Li, Jiang; Liu, Yang (Frontiers in Earth Science, 2023)
Replacing protective inter-block coal pillars (PICPs) with cemented artificial pillars is proposed here to address low coal recovery rates. The use of cemented artificial pillars also reduces resource waste when PICPs are used in the short-wall block mining (SBM) process. A coal mine test area in northern Shaanxi, China, was employed as the study site. Artificial pillar replacement techniques were developed based on the layout characteristics of a typical SBM workface. High-strength cemented backfill materials for artificial pillars were manufactured using innovative material ratio testing, and the optimum ratios for backfill materials are discussed. A cusp catastrophe model of an artificial pillar was then developed and used to deduce the conditions and critical widths necessary to generate catastrophic instability of an artificial pillar. This theoretical analysis was validated using FLAC3D simulations. Using the test site conditions, the simulations revealed that when an artificial pillar had a width of 14 m, the destruction of the pillar and associated stope was gradual and would not cause catastrophic instability. Field monitoring performed at the test site verified the theoretical analysis and numerical simulation results, confirming that it was feasible to replace PICPs with cemented artificial pillars.